THE INFLUENCE OF LEADERSHIP STYLE, WORK MOTIVATION AND JOB STRESS ON EMPLOYEE PERFORMANCE AT PT. BANK SUMUT MEDAN HEAD OFFICE (CASE STUDY ON CREDIT ADMIN LEGAL OPERATIONAL DIVISION) - Wolfgang Alfredo Lumbantobing; Sirojuzilam; Iskandarini (RADJA PUBLIKA, 2023)
Employee performance is the result of implementing the goals of an organization, therefore good performance is an important thing for all employees to do. This research aims to determine the influence of leadership style, work motivation and work stress on the performance of PT employees. Bank Sumut Medan Head Office in the credit admin legal operations division. This type of research is quantitative. The data source was obtained through distributing questionnaires to employees at PT. Bank Sumut Medan Head Office in the credit admin legal operations division. The population and saturated sample in this study were 50 employees at PT. Bank Sumut Medan Head Office in the credit admin legal operations division. The analysis technique used is multiple linear regression analysis technique. The results of this research indicate that partially leadership style, work motivation and work stress influence employee performance. Simultaneously leadership style, work motivation and work stress influence employee performance by 61.8%, while the remaining 38.2% is influenced by other factors not included in this research.